Hisbah dalam Praktik Diskon Palsu pada Platform E-Commerce - Dewi Mutmainnah (Journal of Management and Social Sciences, 2024)
E-commerce represents the largest sector within Indonesia's digital economy, with a Gross Merchandise Value (GMV) of USD 62 billion in 2023, projected to grow to USD 82 billion by 2025. However, amidst this rapid growth, the practice of deceptive discounts—manipulating prices to create the illusion of significant price cuts—frequently occurs, causing harm to consumers. Such practices are inherently at odds with the principles of honesty and fairness in Islamic economics. This study examines the role of hisbah in monitoring and preventing deceptive discount practices in e-commerce. The primary objective of this research is to propose solutions to address the prevalence of deceptive discount practices on e-commerce platforms. The study employs a qualitative approach through library research. Data were gathered from primary and secondary literature, including books, journal articles, regulations, and related documents. The analytical method used is descriptive-analytical, aimed at understanding the relevance and application of hisbah principles in the oversight of e-commerce. The findings reveal that hisbah can complement existing regulations by emphasizing moral supervision, social sanctions, consumer education, and policy advocacy grounded in Islamic values. The implementation of hisbah not only ensures transactional integrity but also fosters an e-commerce ecosystem that is fair, transparent, and aligned with Sharia principles.